The collapse of the Ottoman Empire and the partition of the Middle East, 1879-1919. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
This collection is drawn from the personal papers of Mark Sykes (1879-1919), a politician and diplomatic advisor famous for his role in the partition of the Middle East around the period of the First World War. He is best known for his role in the Sykes-Picot Agreement of 1916, which was a secret treaty between European powers that divided up the Ottoman Empire in the face of its impending collapse. In addition to material related to the Sykes-Picot Agreement, the papers focus on Sykes' experience in military intelligence and diplomacy in the Middle East, both before and during the First World War. This includes touching on such historic events like the Armenian genocide as well as international debates around Zionism and the creation of a Jewish homeland. As an avid explorer, of a more personal nature are his notebooks, which offer an insight into the experience of an aristocratic traveler in the Middle East during the early 20th century.
Date range: 1879-1919.
Keywords: Middle East -- History; Israel -- History; Asia Minor Agreement (1916).; Turkey -- History -- Ottoman Empire, 1288-1918.